The history of the peopling of the "Roof of the World": understanding the early occupation of the Tibetan Plateau through archaeological records - Jegateesh S/O Gynasigamani (Nanyang Technological University, 2024)
Despite its seemingly impossible topography, the Tibetan Plateau (TP) plays host to some of the highest known settlements anywhere in the world today. Yet, impressively, archaeological records indicate that Tibetans have long dwelt amidst the hypoxia-inducing elevations atop the TP. The early peopling of the TP therefore stands to contribute much towards our understanding of prehistoric human migrations and hence constitutes an exciting frontier for historical research. This interdisciplinary study argues that while Anatomically Modern Humans (AMH) may have first reached the TP sometime preceding the Last Glacial Maximum (LGM), it is more so likely that permanent colonisation of the high-altitude regions of the TP was only achieved after the fact -- possibly during the time of the Tibetan-Han population divergence between 15,000 years and 9,000 years B.P. This would likely be enabled by an amalgamation of instrumental factors such as the general increase in temperature within the higher reaches of the TP following the end of the LGM, the subsequent spread of agriculture across the plateau and possible gene introgression events between extant archaic hominins based in the TP and AMH that granted the latter the necessary genetic prerequisites to code for vital high-altitude and hypoxia-resistant adaptations.